Stroke associated with giant cell arteritis: a population-based study. Issue 2 (29th April 2014) - Samson, Maxime; Jacquin, Agnès; Audia, Sylvain; Daubail, Benoit; Devilliers, Hervé; Petrella, Tony; Martin, Laurent; Durier, Jérôme; Besancenot, Jean-François; Lorcerie, Bernard; Giroud, Maurice; Bonnotte, Bernard; et al.
Abstract : Background: Giant cell arteritis (GCA) is the most common vasculitis in people ≥50 years and can be associated with stroke. We aimed to evaluate the epidemiology and characteristics of stroke in patients with GCA. Methods: All patients with a biopsy-proven diagnosis of GCA were identified among residents of the city of Dijon, France (152 000 inhabitants), between 2001 and 2012 using a prospective database. Among these, patients who suffered from stroke were retrieved by crossing data from the population-based Dijon Stroke Registry. Demographics and clinical features were recorded. We considered that the stroke was GCA-related if the stroke revealed GCA or occurred between the onset of symptoms and 4 weeks after the start of treatment. Results: Among the 57 biopsy-proven patients with GCA (incidence rate 10.9/100 000/year in individuals ≥50 years), 4 (7.0%) experienced a GCA-related stroke. Three were men and all had ≥2 vascular risk factors and were ≥80 years. The stroke was vertebrobasilar for 3/4 patients and undetermined for the remaining one. The incidence rate of GCA-related stroke in patients ≥50 years was 0.76/100 000/year (95% CI 0 to 2.47), 1.36/100 000/year in men (95% CI 0 to 3.63) and 0.33/100 000/year (95% CI 0 to 1.45) in women. Conclusions: This population-based study demonstrated that GCA-related stroke essentially affects the vertebrobasilar territory and mainly occurs in old men with associated vascular risk factors. Although rare, GCA symptoms must be searched for in elderly patients with stroke, and optimal vascular prevention must be conducted carefully in patients with GCA with a high vascular risk before initiating GCA treatment.